PENGARUH KOMPETENSI MANAJERIAL KEPALA SEKOLAH TERHADAP KINERJA PENDIDIK DI SEKOLAH DASAR - Salamah, Salamah (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
Principal managerial competence is one of the competencies possessed and implemented by the Principal in designing, compiling and implementing administrative plans and educational activities within a predetermined time period. There is a task carried out by the Principal so that all components run according to a predetermined plan and achieve mutually agreed goals. This research aims to describe the influence of the Principal’s managerial competence on the performance of educators at the primary school level. The research method used is an ex post facto research method with a correlation design. Data collection techniques were carried out through observation, interviews, and distributing questionnaires. The sample for this research was 15 school Principals and 30 Teacher at the primary school level in the Mojotengah subdistrict, Wonosobo Regency, Central Java. The results of this research reveal that the Adjusted R Square (Coefficient of Determination) value was 0.410. This means that there is a 41% influence of the Principal’s managerial competence on the performance of Teachers. Based on the research results that have been presented, it can be concluded that there is a significant positive influence between the managerial competence of the Principal and the performance of Teacher.